Ionization and star formation in the giant H II region SMC-N66 - Geist, Emily; Gallagher, John S.; Kotulla, R.; Oskinova, Lidia M.; Hamann, W.-R.; Ramachandran, Varsha; Sabbi, Elena; Smith, L.; Kniazev, A.; Nota, A.; Rickard, M. J. (Publications of the Astronomical Society of the Pacific, 2022)
The NGC 346 young stellar system and associated N66 giant H ii region in the Small Magellanic Cloud are the nearest example of a massive star-forming event in a low metallicity (Z ≈ 0.2Z ⊙) galaxy. With an age of ≲3 Myr this system provides a unique opportunity to study relationships between massive stars and their associated H ii region. Using archival data, we derive a total Hα luminosity of L(Hα) = 4.1 × 1038 erg s−1 corresponding to an H-photoionization rate of 3 × 1050 s−1. A comparison with a predicted stellar ionization rate derived from the more than 50 known O-stars in NGC 346, including massive stars recently classified from Hubble Space Telescope far-ultraviolet (FUV) spectra, indicates an approximate ionization balance. Spectra obtained with SALT suggest the ionization structure of N66 could be consistent with some leakage of ionizing photons. Due to the low metallicity, the FUV luminosity from NGC 346 is not confined to the interstellar cloud associated with N66. Ionization extends through much of the spatial extent of the N66 cloud complex, and most of the cloud mass is not ionized. The stellar mass estimated from nebular L(Hα) appears to be lower than masses derived from the census of resolved stars which may indicate a disconnect between the formation of high and low mass stars in this region. We briefly discuss implications of the properties of N66 for studies of star formation and stellar feedback in low metallicity environments.
Gesehen am 08.09.2022